How CSR creates value for mutual insurers: a strategic-economic model for managers - Lageu, Faye (2009)
Over the last 20 years, corporate social responsibility (CSR) has worked its way up the business and political agenda. Evidence of firms’ increased CSR investments are not matched,however, by clear evidence of how CSR creates value for firms.